Validity of the Physical Activity Questionnaires IPAQ-SF and GPAQ for Cancer Survivors: Insights from a Spanish Cohort - Ruiz-Casado, A.; Alejo, L. B.; Santos-Lozano, A.; Soria, A.; Ortega, M. J.; Pagola, I.; Fiuza-Luces, C.; Palomo, I.; Garatachea, N.; Cebolla, H.; Lucia, A. (International Journal of Sports Medicine, 2016)
Regular physical activity (PA) decreases mortality risk in survivors of breast and colorectal cancer. Such impacts of exercise have prompted initiatives designed both to promote and adequately monitor PA in cancer survivors. This study examines the validity of 2 widely used self-report methods for PA determination, the International Physical Activity Questionnaire short version (IPAQ-SF) and Global Physical Activity Questionnaire (GPAQ). Both instruments were compared with the triaxial accelerometry (Actigraph) method as an objective reference standard. Study participants were 204 cancer survivors (both sexes, aged 18–79 years). Compared with accelerometry, both questionnaires significantly overestimated PA levels (across all intensities) and underestimated physical inactivity levels. No differences were detected between the 2 questionnaires except for a shorter inactivity time estimated by GPAQ (p=0.001). The Bland and Altman method confirmed that both questionnaires overestimated all PA levels. Receiver operating characteristic (ROC) analysis classified IPAQ and GPAQ as fair and poor predictors, respectively, of the proportions of survivors fulfilling international PA recommendations (≥150 min·week−1 of moderate-vigorous PA). IPAQ-SF showed a higher sensitivity but lower specificity than GPAQ. Our data do not support the use of IPAQ-SF or GPAQ to determine PA or inactivity levels in cancer survivors.
Keywords: tumor; self-reported physical activity; physical inactivity; accelerometer